Addition of Eco-enzyme In Lemna minor Cultivation as Alternative Feed to Support SDG 2 in Kampoeng Oase - Lestari, Gadis Suci; Fitrihidajati, Herlina; Candra, Adi; Nurcholis, Nurcholis; Aseyan, Aseyan (Journal of Community Service and Empowerment, 2026)
Catfish farming still faces the problem of high feed costs, so economical and sustainable alternative feeds are needed. Lemna minor has the potential to be used as an alternative feed due to its high nutritional content, but its growth productivity is relatively low without added nutrients. The use of eco-enzymes made from household organic waste as organic liquid fertilizer is a solution to increase the productivity of Lemna minor while supporting sustainable waste management. This study aims to describe the content of eco-enzymes from organic waste, describe the effect and determine the most effective concentration of eco-enzymes in increasing the cover area (LCA) and biomass of Lemna minor, as well as assess its impact as an alternative feed supporting SDG 2. The research was conducted from September to November 2025 at Kampoeng Pintar Oase and consisted of two stages, namely observation of the eco-enzyme production process and experimentation with its implementation in Lemna minor cultivation. The parameters observed included the macro nutrient content of eco-enzymes, cover area (LCA), Lemna minor biomass, and cultivation media quality. Nutrient content analysis was conducted at the Surabaya Laboratory of the Agency for Standardization and Industrial Services (BSPJI) based on the 2011 standard for liquid organic fertilizer quality. The data were analyzed descriptively quantitatively, followed by one-way analysis of variance and Duncan's test at a 5% level. The results showed that eco-enzyme met the standards for liquid organic fertilizer and had a significant effect on the growth of Lemna minor. A concentration of 20 ml of eco-enzyme produced the highest LCA and biomass values, while a concentration of 60 ml showed the lowest growth. These findings indicate that eco-enzyme at the optimal concentration effectively increases Lemna minor production and supports sustainable food security in line with SDG 2.